Data on the bat fauna of the Northern Black Sea Region based on results of the work of bat contact centres - P. Panchenko; L. Godlevska (Theriologia Ukrainica, 2018)
During 2009–2018, 201 calls were received by the Odesa contact centre, OCC (n = 174, in 143 of them bat species was identified) and the Kyiv contact centre, KCC, from the Northern Black Sea Region (n = 27; 10, with an identified species). The majority of calls (94 %) to the OCC came from Odesa region. The number of calls and its increase in time confirms the demand for bat contact centres, especially regional ones, and their role as an instrument of fauna research and monitoring, in particular in urban landscapes. The majority of calls with identified species obtained from south-western Ukraine (Odesa, Mykolayiv and Kherson regions) dealt with four species: Pipistrellus kuhlii (34 %), Nyctalus noctula (23 %), Eptesicus serotinus (21 %), and Vespertilio murinus (13 %). In addition, two more species were recorded: Pipistrellus nathusii and Plecotus austriacus (6 and 3 %, respectively). For the first time, in Odesa region P. nathusii was recorded in winter. Repeated winter records of this species are evidence of its wintering in Odesa region.